Unsuccessful in vitro regeneration from Phalaenopsis (Orchidaceae) flowers (The All Results Journal, 2014)
Regeneration in vitro has never been achieved from flower parts from members of the Orchidaceae and no report exists for Phalaenopsis. Studies that do exist all used immature (unopened) flower buds. In a bid to overcome this hurdle, in vitro organogenesis was attempted with various parts (dorsal sepal (base + center + tip); petal (base + center + tip); lateral sepal (base + center + tip); labellum (base + center + tip); pedicel (outer + inner tissue); column; anther cap; stigmatic surface) of immature and fully opened Phalaenopsis Gallant Beau ‘George Vazquez’ flowers. Despite the use of an extremely wide selection of plant growth regulators in Vacin and Went basal medium, and their concentrations, in both darkness and light conditions, no organogenesis could be achieved from any of the flower parts tested. Some callus was obtained on the column in response to 2 or 4 mg/l TDZ in the light, or to 1 mg/l 2,4-D and 1 mg/l dicamba in the dark, but the callus was hard and could not be further proliferated or induced to form organs. Although negative, these trials provide encouraging signs that organogenesis may be possible from flower parts with a little more insistence. To be able to achieve such regeneration would potential allow for the generation of haploid or polyploidy plants which may have practical use in orchid breeding and biotechnology if such plants (or plant parts) can be clonally propagated.